Ab initio investigation of B16(GeS), B27(FeB) and B33(CrB/TlI) phases of lead chalcogenides - Demiray, Ferhat; Berber, Savas (Iop Publishing Ltd, 2013)
We report an ab initio investigation of the intermediate phases occurring in the pressure-induced B1-B2 phase transitions of lead chalcogenides PbX (X = S, Se and Te). The equilibrium lattice constants and atomic positions were calculated without symmetry constraints. The total energies of the optimized structures under pressure were obtained to determine the structures of possible intermediate phases and transitions between these structures. PbTe prefers to be in the B27 structure in the whole transition pressure range while the intermediate phase of PbSe is B27 at lower pressures and becomes B16/B33 at approximate to 5 GPa. Our results help in understanding the difficulties in experimental investigations of the intermediate phase of PbSe. The intermediate phase of PbS is in the B27 structure at lower pressure values, but it should be in the B16/B33 structure with a transition around approximate to 6 GPa. Our finding that it is possible to find the intermediate structures of PbS and PbSe in B27 and B16/B33 while PbTe adopts only B27 as the intermediate structure is in good agreement with previous research. The electronic structures of the three structures remain semi-conducting in their calculated optimized structures and the fundamental electronic energy gap decreases with increasing pressure. The projected density of states indicates that the bonding between the Pb atom and the chalcogen has both covalent and ionic contributions with a charge transfer from the Pb atom to the chalcogen.
Keywords: High-Pressure Phases; Electronic-Structure; Band-Structure; Pbs; Pbte; Sulfide; Semiconductors; Diffraction; Transitions; Parameters